The Role of External Knowledge in the Innovative Activities of Agricultural Biotechnology Multinationals - Ribeiro, Fernanda Teixeira Franco; Figueira, Mariane; Calegario, Cristina Lelis Leal (Internext, 2021)
Objective: To evaluate the influence of external knowledge absorbed on the potential to innovate of multinational companies (MNCs), in the genetically modified (GM) seed sector from 2000 to 2018. Method: A quantitative approach was applied. Data was composed of the main patents filed by MNCs in the GM seed sector, collected from the Espacenet database, the MNCs’ annual reports, and the INPI database. Variables were analyzed using panel regression model. Main results: Results showed that the MNCs’ own resources, as well as the external knowledge absorbed were individually significant. The Interactive variable was not significant in the model. Relevance/ Originality: In addition to addressing literature gaps related for instance to the need to investigate the factors that influence the generation of innovation in multinationals, the present study focused on the agricultural biotechnology sector, which is of paramount importance for the innovations generated in agriculture. Theoretical contributions: This study contributes by filling literature gaps related to the need to understand how important is the influence of the external knowledge and resources to the innovative capabilities of MNCs. Social contributions: This paper helps managers be conscious of the fact that innovation is not only developed internally, involving the MNC’s own network, but in fact, innovation requires relationships with other companies, allowing the access of external knowledge and resources.